Analisis Fenomena Budaya Foto Pre-Wedding Di Masyarakat: Studi Takhrij dan Syarah Hadis - Rosa, Elsa Martina (Jurnal Riset Agama, 2022)
This study aims to discuss the hadith syarah about seclusion regarding the phenomenon of the rise of pre-wedding culture in society. This study uses a qualitative approach that emphasizes literature review through the takhrij and syarah hadith methods. The results of this study found that the quality status of the hadith about seclusion is authentic. This hadith is judged authentic because all narrators are dzabit and fair (tsiqot) and because it is authentic and valid, this hadith is considered maqbul (accepted) so that it can be practiced. The conclusion of this study is that pre-wedding that is rampant in society contains elements of seclusion. Since the time of the Prophet, seclusion has been forbidden because it invites heinous acts. Therefore, the law of pre-wedding is haram. Except if there are no elements prohibited by the Shari'a and the intention is only to make it easier for the invited guests to recognize the bride and groom.